2017
DOI: 10.1177/0194599817718782
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Eczematous External Otitis with Honey Eardrops: A Proof‐of‐Concept Study

Abstract: Eczematous external otitis is a chronic inflammatory disease and often difficult to treat. Our objective was to investigate the clinical effect and in vitro antibacterial potential of medical honey eardrops as treatment of eczematous external otitis. In a prospective study, 15 patients diagnosed with recurrent eczematous external otitis were treated with medical honey eardrops for 2 weeks. The following clinical outcomes were evaluated: visual analog scale of ear complaints, score of eczema, and eradication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…In the trial carried out by Kwakman and coworkers, the medical-grade honey did not affect colonization of the skin at central venous catheter insertion sites in intensive care units patients when applied in addition to standard disinfection with 0.5% chlorhexidine in 70% alcohol [ 49 ]. The outcomes of investigation carried out by the mentioned above group of Henatsch revealed that honey eardrops showed a strong in vitro inhibitory activity against all tested strains but did not eradicate S. aureus infection in vivo [ 50 ]. It also should be emphasized that in vivo infections are often caused by bacteria growing in the form of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In the trial carried out by Kwakman and coworkers, the medical-grade honey did not affect colonization of the skin at central venous catheter insertion sites in intensive care units patients when applied in addition to standard disinfection with 0.5% chlorhexidine in 70% alcohol [ 49 ]. The outcomes of investigation carried out by the mentioned above group of Henatsch revealed that honey eardrops showed a strong in vitro inhibitory activity against all tested strains but did not eradicate S. aureus infection in vivo [ 50 ]. It also should be emphasized that in vivo infections are often caused by bacteria growing in the form of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Honey has been long appreciated for its exceptional ability to de-escalate phlogosis, hence the traditional use as a medicament on chronic inflammatory skin conditions and in the management of persistent symptoms such as unremitting discomfort, itchiness often associated with skin abrasion, and laceration due to scratching, all severely affecting the quality of patients' everyday life. Along with the conventional treatments prescribed to soothe the affected skin (predominantly topical corticosteroids), growing interest has been expressed for natural remedies in the management of disorders with a main inflammatory component such as eczematous lesions and psoriasis [103,104]. Alangari et al researched the performance of Manuka honey on atopic dermatitis (AD) patients and tried to elucidate the responsible biochemical mechanisms by AD-related in vitro models.…”
Section: Anti-inflammatory Properties Of Honeymentioning
confidence: 99%
“…Eczematous otitis externa is the sequel of hypersensitivity to certain organisms that are infectious or, some eardrops. It is marked by intense vexation, forming of vesicles, oozes and, crusts in the ear passage [11].…”
Section: Clinical Featuresmentioning
confidence: 99%